Pengaruh Kadar Air Terhadap Tingkat Keasaman Tanah Kampung Burmeso Secara Elektrometri - Sineri, Carli N. M.; Krimadi, Lodwyk N.; Salim, Ilham; Mandik, Yohanis I.; Rusmanta, Yohanes B. J. (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
A study has been conducted on the analysis of the effect of moisture content on the acidity level (pH H2O and pH KCl) of the soil of Burmeso Village using the electrometry method. Samples were taken from a depth of 0-10 cm with a sample soil ring. Next, the soil samples were dried at 105°C for 3 hours, sifted using a 200 mesh sieve. The analysis was carried out on the physical properties (moisture content) and its correlation with the chemical properties (Soil Acidity). The results of this study showed that the soil moisture content of three soil samples was 9.03 (TL), 9.065 (TH), and 9.56 (TB) and was classified as high enough moisture content so that it had a direct effect on the pH of farmland, forest soil and ex-field soil was classified as sour (low) to slightly sour (moderate), the high and low pH greatly affected the nutrient content in the soil so that it produced. The results of soil acidity analysis also indicate that the actual acidity pH value (H2O pH) is greater when compared to the potential pH (pH KCl) so that the ΔpH value tends to be negative including -0.705 (TL), -0.84 (TH), and -1.035 (TB), this negative value shows that the soil of Burmeso Village is a negative net load soil occupied by exchangeable bases (KTK).